Implementation of ESG (Environmental, Social, Governance) in HRM Practices: A Study on Sustainable Companies in Indonesia - Burhanuddin, Burhanuddin (International Humanity Advance, Business & Sciences, 2025)
This qualitative study examines the integration of Environmental, Social, and Governance (ESG) principles into Human Resource Management (HRM) practices within sustainable companies in Indonesia. As the global focus on sustainability intensifies, organizations are increasingly expected to align their HR strategies with ESG objectives. The research aims to explore the current practices, challenges, and opportunities faced by companies in Indonesia as they seek to incorporate ESG into their HR frameworks. Using a multi-site case study approach, data was collected through in-depth interviews with HR managers, line managers, and employees, as well as document analysis (sustainability reports, HR policies) and participant observation. Three companies, including large organizations like Unilever Indonesia and Bank Mandiri, as well as green-tech startups, were selected for this study. The findings reveal that while there is a growing awareness and commitment to ESG, significant barriers remain, including limited resources, lack of employee engagement, and organizational resistance. The research contributes to the understanding of how ESG is shaping HRM practices in Indonesia and offers recommendations for organizations aiming to enhance their sustainability efforts through effective HR strategies.